Research of the second pneumeseparating channel of the machine for preliminary grain cleaning MPO-30R «VELES» - A. L. Glushkov; Yu. V. Sychugov; V. A. Lazykin (Аграрная наука Евро-Северо-Востока)
In 2017 in the Kirov region the research of the second pneumо separating channel of the machine MPO-30R «VELES» intended for preliminary cleaning of the grain heap of grain crops, cereals, legumes, maize, sorghum, sunflower, as well as for primary and secondary clearing of the grain of these crops from impurities in all agricultural zones of the country was carried out. This was done in order to study the impact of structural and technological parameters of this channel on the effect of cleaning the grain material from light impurities and determining the optimal values of the parameters studied. Experimental studies were carried out by conventional methods in three modes: preliminary, primary and secondary cleaning of grain. As a result of the research of the pneumо separating channel of the mass-produced machine MPO-30R «VELES» it has been established that installation of deflector rods in the lower part of the channel reduces average speeds of an air stream, increases unevenness of a field of speeds in the separation zone that leads to deterioration of cleaning quality of the grain material. The effect of cleaning the grain material from light impurities when installing deflector rods is reduced by 12.8% in the pre-cleaning mode, by 8.8% in the primary cleaning mode and by 2.7% in the secondary cleaning mode. Research of the pneumо separating channel with a modified bottom part proved that with increasing depth of the bottom of the channel from 0.13 to 0.16 m the effect of cleaning of the grain material from light impurities in the mode of preliminary cleaning increased by 8.0 %; of primary cleaning - by 3.8 % and of the secondary cleaning - by 7.4% with a relatively equal loss of high-grade grain to waste. Thus, taking into account the maximum values of the effect of cleaning the grain material from light impurities, the lower part of the pneumо separating channel should be made straight, inclined at an angle of 13° to the vertical, without deflector rods. The depth of the lower part of the channe l, taking into account the maximum capacity of the fan (2.14 m3/s) and the required average speed of the air flow in the pneumо separating channel for the secondary cleaning of grain (8.0 m/s) should be 130 mm.